The Role of Bhabinkamtibmas in Preventing the Crime of Motor Vehicle Theft in the Legal Territory of the Kebumen Police - Yunia Setioningrum (Police Studies Review, 2021)
This research is motivated by the crime of motor vehicle theft (curanmor) in Kebumen Regency which is relatively high. Repressive efforts against theft cases do not solve the problem, so the most effective efforts are preventive and preemptive efforts. Therefore, a study was conducted that aims to determine the general description of theft, the role of Bhabinkamtibmas and the factors that influence the role of bhabinkamtibmas in preventing theft in Kebumen Regency. The literature review used by the author is the research literature from the 2017 Akpol alumni thesis Dwi Dea Anggraini and Bagus Aji Setiawan and the conceptual literature in the form of the bhabinkamtibmas concept, the concept of prevention, the concept of motor vehicle theft, management theory and role theory. This type of research is descriptive with a qualitative approach that focuses on the role of bhabinkamtibmas in preventing theft. The research location is in the jurisdiction of the Kebumen Police, using primary and secondary data sources as well as data collection techniques by interviewing, observing, and documenting studies. The data analysis technique uses data reduction, data presentation and conclusions, while the data validity uses triagulation techniques. This study produces data in the form of a general description of theft in Kebumen Regency including place, time and vulnerable areas, the modus operandi that is often used, the brand of the vehicle and the age of the perpetrator of the theft. The role of bhabinkamtibmas is carried out through bintibmas, binkamsa, binpolmas and binpotmas activities, while the influencing factors come from human factors (bhabinkamtibmas), facilities and infrastructure, methods, budgets and community responses. The conclusion of this study is that theft in Kebumen Regency occurred in residential areas in Buluspesantren District at around 03.00-06.00 WIB with the modus operandi using the "T" key, the age of the perpetrators ranged from 18-30 years and the vehicle brand was Honda Beat. The role of bhabinkamtibmas is carried out through bintibmas, binkamsa, binpolmas and binpotmas activities. The influencing factors are the number of bhabinkamtibmas that are lacking and concurrent positions, inadequate facilities and infrastructure, inappropriate methods, poor public response and adequate budget. While the suggestions given by the author are in the form of good communication between the Binmas unit and the Criminal Investigation Unit, optimizing the role of Bhabinkamtibmas, cooperation between Babinkamtibmas with the community and government as well as providing rewards and punishments for high achieving bhabinkamtbmas and reprimands.